Conduction defect rates in high risk surgical patients undergoing TAVR with or without PCI during a single hospitalization: a nationwide study. (25th November 2020) - Zarrabian, B; Byer, M; Celli, D; Colombo, R
Abstract: Introduction: Since the first documented transaortic valve replacement (TAVR) by Cribier et. al. in 2002 as a less invasive treatment approach for severe aortic stenosis (AS) and following the landmark PARTNER 1 trial, the Food and Drug Administration (FDA) approved TAVR in 2012 for patients deemed to be at high surgical risk. In recent years, there has been an expansion of indications to include low surgical risk candidates. Risk factors associated with aortic stenosis overlap with those for coronary artery disease, and up to 40–70% of patients referred for replacement have incidental obstructive coronary lesions. The best timing of intervention for concurrent pathology has been a subject of debate; recommendations support combined TAVR and percutaneous coronary intervention (PCI) for treatment of ostial/proximal lesions or in unstable patients. TAVR is not free of complications and a concern has been on post-deployment alterations of the heart's electrical system that may result in need for permanent pacemaker (PPM) implantation. Purpose: To secure the aortic valve in place during a TAVR, there is a known risk of inducing a conduction disturbance. This study examined conduction abnormalities in patients undergoing a concurrent TAVR and PCI during the same hospitalization. Methods: The patient population was obtained from the Nation Inpatient Sample database, which is a stratified systematic random sample of 20% hospital admissions in the USA. ICD-9 Revision-Clinical Modification procedure codes were used to identify all patients undergoing PCI and TAVR during the same admission between 2011 and 2014. Patients 50 years and older were included. Those with a history of a PPM were excluded. Outcomes of interest included new PPM, left bundle branch block (LBBB), first degree/second degree/complete AV bock, all-cause in-hospital mortality, and length of stay. Multivariate logistic regression analysis was used while adjusting for patient and procedural confounders. Results: Between 2011 and 2014, 29, 998 patients underwent TAVR, of which 1070 had a concurrent PCI during the same hospital admission. There was no noted increase in odds of PPM (OR 0.42 95% CI: 0.010–1.72), LBBB (OR 1.89 95% CI 0.65–5.49), second degree AV block (OR 1.49 95% CI: 0.21–10.50), complete AV block (OR: 1.44, 95% CI: 0.57–3.63), atrial fibrillation (OR 0.95 95% CI: 0.46–1.94), or atrial flutter (OR 1.75 95% 0.38–7.94) in those undergoing PCI+TAVR compared to TAVR alone. The odds of all cause, in-hospital mortality was 4.44 (95% CI: 1.25–15.8) times greater in those with a PCI+TAVR during the same admission compared to TAVR alone. Length of stay was 7.5 days (95% CI: 7.25–7.75) in those undergoing a TAVR compared to 12.4 days (95% CI: 10.67–14.15) in those with a TAVR+PCI, p<0.0001. Conclusion: Periprocedural PCI and TAVR during the same hospitalization does not further increase risk of major conduction defects or rates of pacemaker implantation. Funding Acknowledgement: Type of funding source: None